Deaths due to motorcycle accidents in Teresina, Piauí State, Brazil - Noronha, Cláudia Karine Carmo de (2011)
ABSTRACT Currently, the incidence of traffic accidents has been reaching new heights and is considered one of the main causes of worldwide deaths. Moreover, millions of people die every year due to such fatalities, which cause family disruptions, psychological damage and increases in social costs in several countries. Among these traffic accidents, motorcycle accidents are of significant importance due to the body exposure of the riders, which can lead to severe sequelae and even death. Given these issues, this study aimed at characterizing the fatal victims of motorcycle accidents reported at the Delegacia de Repressão aos Crimes de Trânsito (Traffic Crimes Repression Unit) in the City of Teresina, Piauí State, Brazil, in addition to determining the sociodemographic profile of these victims, describing the type of collision and the most frequent sites of accidents. This descriptive study used retrospective documentary analysis and a quantitative approach and was developed in the City of Teresina. The source included 86 accidents reported at the aforementioned Unit in 2009. The study was approved by the Ethics Committee of the Faculdade Integral Diferencial, protocol no 358/10. Our results revealed a higher exposure of males to accidents, and the predominant age group was young adults. A prevalence of incidents on public roads with intense movement and a higher incidence of accidents in March were also observed. Because of the significant increase of this type of accident, we conclude that the implementation of effective public policies for the monitoring and control of these accidents and investments in health education preventive actions are essential to raise population awareness.